Supply Chain Management and Advanced Planning - Stadtler, Hartmut; Kilger, Christoph; Meyr, Herbert (Springer, 2015)
More than 15 years have passed since we started working on the first edition of this book. A lot has happened in the meantime. A dot-com bubble has grown and burst. Another wave of lean management has rolled over the planning landscape. Some people still seem to think that Advanced Planning and Lean Management are exclusive philosophies although the automotive industry—as the prime father to Lean—is the best example that both can and should complement each other in a fruitful co-existence and synergy. New buzz words like profit velocity, demand sensing and service oriented architecture have come and gone. Often they disappeared even faster than they have risen. During the 7 years since publishing our fourth edition consolidation on the Advanced Planning Systems’ (APS) software market continued at an unabated pace. Thus, we decided to do some historical research and inserted a sort of genealogical tree of APS in Chap. 16—in addition to our traditionally updated and extended overview of selected software systems in Chap. 18. The term “Sales & Operations Planning” is actually known for more than 25 years in the scientific literature. Nevertheless, during recent years it came up as a renewed concept on the software and consulting market.We will discuss how this old idea is interpreted in a modern software world within several chapters. Chapters 6 on Strategic Network Design, 8 on Master Planning and 12 on Transport Planning partly show new authors. This gave reason to restructure and revise their contents substantially.With a new case study of the specialty chemicals industry (Chap. 26), we do not only welcome another new author, but also will have a closer look at a “new” software suite and software vendor (at least as this book is concerned). Of course a lot of further updates have been made—by far too many to be mentioned in this preface. Finally, a new editor has been affiliated. He not only was an author since the first edition, but also acted as an editor of the German translation of “our” book in 2011. Thus, do not be surprised to find a third signature below this preface.
Concepts, Models, Software, and Case Studies